Peran Guru BK dalam Perencanaan Karier Siswa SMK dengan Mengunakan Layanan Tes Bakat Minat - Tahlita Naura Yafi; Mayva Irwan Salsabila; Noni Bela Maulida (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Career planning is a crucial step in equipping vocational high school students to face the world of work or continue their education. This study aims to explain the role of Guidance and Counseling (BK) teachers in helping students plan their careers through aptitude and interest test services. This study uses a narrative qualitative approach using data collection techniques through literature studies and content analysis. The study that will take place shows that BK teachers have a strategic role in helping students recognize their potential, determine educational paths, and choose the appropriate career direction using their abilities and interests. Aptitude and interest tests are important instruments that help students understand personal strengths and reduce the risk of mis-majoring. Barriers to the implementation of these services include limited resources, test sense, and lack of career issues. Therefore, an integrated strategy is needed between BK teachers, schools, and parents so that this service can run optimally.